PENGARUH MEDIA PEMBELAJARAN BERBASIS GAME WORDWALL TERHADAP HASIL BELAJAR GEOGRAFI PESERTA DIDIK FASE E DI SMAN 1 PADANG GELUGUR - Seftiana, Lelly; Loli Setriani; Ade Irma Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the minimal utilization of Information and Communication Technology (ICT) in learning activities, particularly concerning the use of interactive learning media. This has become a crucial issue because it affects the students' learning outcomes, which are not yet optimal. At SMAN 1 Padang Gelugur, it was found that students' learning outcomes in Geography have not yet reached the Learning Objective Achievement Criteria (KKTP). This condition encourages research to find effective solutions, one of which is through the innovation of learning media. This study aims to examine the influence of Wordwall game-based learning media on Geography learning outcomes for Phase E students at SMAN 1 Padang Gelugur. We used a quantitative approach with an experimental method to objectively measure the impact of the media's use. The population of this study includes all Phase E students at SMAN 1 Padang Gelugur. Meanwhile, the sample was specifically divided into two groups, namely class E.3 as the control class and E.9 as the experimental class. To analyze the data, we used descriptive analysis techniques and the t-test statistical test. Based on the data analysis results, the average learning outcome score in the control class was 78.27, while in the experimental class using the Wordwall media, the average was much higher at 88.82. The t-test results showed a value of 7.131 with a significance level of 0.000 < 0.05. This significance value indicates that the Alternative Hypothesis (Ha) is accepted, meaning there is a significant difference between the learning outcomes of the two classes. Thus, it can be concluded that the Wordwall game-based learning media has a significant and positive impact on the improvement of Geography learning outcomes for Phase E students at SMAN 1 Padang Gelugur. Keywords: Learning Media, Wordwall, Learning Outcomes, Geography, Quantitative, T-test, Information and Communication Technology, Phase E.